Etika Media Sosial dalam Tinjauan Hadis: Studi atas Penyebaran Hoax dan Ujaran Kebencian - Zahid, Azka; Eti Kamala Sari; Lukmanul Hakim (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2025)
This article to explain the development of social media in the digital era has brought significant benefits, but also presents ethical challenges such as the spread of Hoax es and hate speech. This study aims to examine these phenomena through the lens of the hadiths of Prophet Muhammad to establish normative foundations for ethical social media use. Employing a qualitative approach with the library research method, this study draws on primary data in the form of hadiths related to honesty, prohibition of lying, and communication ethics, as well as secondary data from contemporary literature on digital communication. The analysis is carried out using a descriptive-analytical method with a thematic (maudui’) approach. The findings reveal that hadith values such as the principle of ṣiddiq (truthfulness), prohibition against spreading everything one hears, and the encouragement to speak good or remain silent are highly relevant in addressing the spread of Hoax es and hate speech. These values can be implemented to promote ethical and responsible behavior in social media engagement. The study concludes that the application of hadith teachings offers a constructive solution for shaping a healthy and harmonious digital space, and represents Islam’s contribution to addressing the challenges of contemporary communication.